Staphylococcus aureus can use an alternative pathway to be internalized by osteoblasts in absence of β1 integrins - Léo-Paul Tricou; William Mouton; Andréa Cara; Sophie Trouillet-Assant; Daniel Bouvard; Frédéric Laurent; Alan Diot; Jérôme Josse (Scientific Reports)
Abstract Staphylococcus aureus main internalization mechanism in osteoblasts relies on a tripartite interaction between bacterial fibronectin-binding proteins, extracellular matrix soluble fibronectin, and osteoblasts’ β1 integrins. Caveolins, and particularly caveolin-1, have been shown to limit the plasma membrane microdomain mobility, and consequently reduce the uptake of S. aureus in keratinocytes. In this study, we aimed to deepen our understanding of the molecular mechanisms underlying S. aureus internalization in osteoblasts. Mechanistically, S. aureus internalization requires endosomal recycling of β1 integrins as well as downstream effectors such as Src, Rac1, and PAK1. Surprisingly, in β1 integrin deficient osteoblasts, S. aureus internalization is restored when Caveolin-1 is absent and requires αvβ3/5 integrins as backup fibronectin receptors. Altogether, our data support that β1 integrins regulate the level of detergent-resistant membrane at the plasma membrane in a an endosomal and Caveolin-1 dependent manner.